Inhibition of Mammalian Target of Rapamycin Reverses Alveolar Epithelial Neoplasia Induced by Oncogenic K-ras - Marie Wislez; M. Loreto Spencer; Julie Izzo; Denise M. Juroske; Kamna S. Balhara; Dianna D. Cody; Roger E. Price; Walter N. Hittelman; Ignacio I. Wistuba; Jonathan M. Kurie (2005)
Abstract The serine/threonine kinase AKT and its downstream mediator mammalian target of rapamycin (mTOR) are activated in lung adenocarcinoma, and clinical trials are under way to test whether inhibition of mTOR is useful in treating lung cancer. Here, we report that mTOR inhibition blocked malignant progression in K-rasLA1 mice, which undergo somatic activation of the K-ras oncogene and display morphologic changes in alveolar epithelial cells that recapitulate those of precursors of human lung adenocarcinoma. Levels of phospho-S6Ser236/235, a downstream mediator of mTOR, increased with malignant progression (normal alveolar epithelial cells to adenocarcinoma) in K-rasLA1 mice and in patients with lung adenocarcinoma. Atypical alveolar hyperplasia, an early neoplastic change, was prominently associated with macrophages and expressed high levels of phospho-S6Ser236/235. mTOR inhibition in K-rasLA1 mice by treatment with the rapamycin analogue CCI-779 reduced the size and number of early epithelial neoplastic lesions (atypical alveolar hyperplasia and adenomas) and induced apoptosis of intraepithelial macrophages. LKR-13, a lung adenocarcinoma cell line derived from K-rasLA1 mice, was resistant to treatment with CCI-779 in vitro. However, LKR-13 cells grown as syngeneic tumors recruited macrophages, and those tumors regressed in response to treatment with CCI-779. Lastly, conditioned medium from primary cultures of alveolar macrophages stimulated the proliferation of LKR-13 cells. These findings provide evidence that the expansion of lung adenocarcinoma precursors induced by oncogenic K-ras requires mTOR-dependent signaling and that host factors derived from macrophages play a critical role in adenocarcinoma progression.